Prediabetes, elevated iron and all-cause mortality: a cohort study. Issue 12 (11th December 2014) - Mainous, Arch G; Tanner, Rebecca J; Coates, Thomas D; Baker, Richard
Abstract : Objectives: Data have indicated low to non-existent increased mortality risk for individuals with prediabetes, but it is unclear if the risk is increased when the patient has elevated iron markers. Our purpose was to examine the mortality risk among adults with prediabetes in the context of coexisting elevated transferrin saturation (TS) or serum ferritin. Setting: Data collected by the third National Health and Nutrition Examination Survey 1988–1994 (NHANES III) in the USA and by the National Center for Health Statistics for the National Death Index from 1988 to 2006. Participants: Individuals age 40 and older who participated in the NHANES and provided a blood sample. Primary outcome variable: Mortality was measured as all-cause mortality. Results: Adjusted analyses show that prediabetes has a small increased mortality risk (HR=1.04; 95% CI 1.00 to 1.08). Persons who had prediabetes and elevated serum ferritin had an increased HR for death (HR=1.14; 95% CI 1.04 to 1.24) compared with those who had normal ferritin and normal glucose. Among persons with prediabetes who had elevated TS, they had an increased mortality risk (HR=1.88; 95% CI 1.06 to 3.30) compared with those with normal TS levels and normal glucose. Conclusions: The mortality risk of prediabetes is low. However, among individuals who have coexisting elevated iron markers, particularly TS, the risk rises substantially.